The influence of social media marketing on online purchase decisions on Shopee in Bandar Lampung - Alviyandi, Muhammad Rizki; Sari, Aida (Lighthouse Publishing, 2024)
Shopee, as an e-commerce platform in Indonesia, has experienced significant growth in recent years, primarily through the use of digital marketing strategies. One of the most prominent strategies is Social Media Marketing, where Shopee utilizes social media to promote products to consumers. Consumers are frequently exposed to promotional content, reviews, and testimonials from other users, which can influence their purchase decisions. This study aims to investigate the impact of Social Media Marketing on the online Purchase Decisions of Shopee consumers in Bandar Lampung. The data used in this research is primary data obtained through questionnaires distributed to 150 respondents. Sampling was conducted using Nonprobability Sampling with a Purposive Sampling technique. This study applies multiple linear regression analysis and a partial test (t-test). The findings indicate that Social Media Marketing significantly influences consumers’ Purchase Decisions in a simultaneous manner. Partially, the dimensions of Content Creation, Content Sharing, Connecting, and Community Building each have a significant effect on consumers’ Purchase Decisions in Bandar Lampung.